Histomorfometria do corno uterino de gatas (Felis Catus) submetidas à ovariosalpingohisterectomia - Monteiro, Cristina Maria Rodrigues [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Carvalho, Roberto Gameiro de [UNESP]; Silva, Adelina Maria da [UNESP]; Koivisto, Marion Burkhardt [UNESP] (My University, 2012)
Histomorphometric data were obtained from cats uterine horns: either nulliparous (n = 6), primiparous (n = 6), multiparous (n = 6) and treated with contraceptive (n = 6). The material was collected after surgery, fixed in paraformaldehyde and embedded in paraplast® resin to be sliced in a microtome. The obtained sections were stained with hematoxylin - eosin and measured under a light microscope: uterine wall total thickness (μm), endometrium total height, endometrial glands diameter and glandular epithelia height, total myometrium, internal and external myometrium and vascular layer thickness. It was concluded that: 1 - contraceptive use and number of pregnancies altered the uterine structure, 2 - one pregnancy does not appear to affect the uterine lining structures as occurs in multiparous cats, 3 - there was no variation on the evaluated structures between nulliparous and primiparous cats except for inner myometrium, 4 - the total myometrium hight and the endometrium hight showed similar variations except for the contraceptive treated cats group, 5 - the outer myometrium showed marked changes in the treated cats, 6 - the less marked morphological variations were for the endometrial glands diameter and glandular epithelium hight, 7 - the presence of dilated endometrial glands was found only in treated cats.
Histomorphometry of the uterine horn of queens (Felis Catus) uterus submitted to ovaryhisterectomy
Keywords: Births number; Contraceptives; Felines; Uterus; Felis catus